Rekayasa Pernikahan Bagi Muhallil Di Desa Mangar Tlanakan Pamekasan Dalam Perspektif Hukum Islam - Qadariyah, Lailatul (Qanuni : Journal of Indonesian Islamic Family Law, 2024)
This research discusses the practice of muhallil marriage, namely marriage which aims to make the relationship between a husband and wife who have divorced through triple talaq legal. In the case of triple talaq, the husband cannot reconcile unless the ex-wife first marries another man. Some husbands carry out formal muhallil marriages, where the ex-wife marries a third party and then separates after some time, so that she can remarry her first husband. This research uses a qualitative descriptive method through interviews and literature study. The results of the research show that muhallil marriages in Mangar Village, Tlanakan District, Pamekasan Regency are valid according to law, because they fulfill the terms and conditions of marriage without special conditions in the contract. According to Islamic law, muhallil marriages are valid based on the opinions of Imam Syafi'i and Abu Hanifah, although several other schools of thought differ.